2010
DOI: 10.1186/1742-6405-7-34
|View full text |Cite
|
Sign up to set email alerts
|

Lipoprotein levels and cardiovascular risk in HIV-infected and uninfected Rwandan women

Abstract: BackgroundLipoprotein profiles in HIV-infected African women have not been well described. We assessed associations of lipoprotein levels and cardiovascular risk with HIV-infection and CD4 count in Rwandan women.MethodsCross-sectional study of 824 (218 HIV-negative, 606 HIV+) Rwandan women. Body composition by body impedance analysis, CD4 count, and fasting serum total cholesterol (total-C), triglycerides (TG) and high-density lipoprotein (HDL) levels were measured. Low-density lipoprotein (LDL) was calculated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
14
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 26 publications
4
14
1
Order By: Relevance
“…Indeed, HIV infection and antiretroviral drugs have independent noxious effects on the blood-vessels and in association, their impact are significantly worsened (Pontes-Cardoso et al, 2007;Bernal et al, 2008). The reduction of HDL-C in HIV positive of this study confirms report of Bernal et al, (2008), Anastos et al, (2010) and would be due partly to Apo A1 synthesis reduction (Tété-Bénissan et al, 2011), because of immunity collapse (Crowe et al, 2010). In this study, increase of triglycerides in HIV positive is in agreement with report of former studies (Presles, 2006;Pontes-Cardoso et al, 2007;Cournil et al, 2011) which showed that hypertriglyceridemia would be explained by cholesterol and triglycerides transport as lipoproteins.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Indeed, HIV infection and antiretroviral drugs have independent noxious effects on the blood-vessels and in association, their impact are significantly worsened (Pontes-Cardoso et al, 2007;Bernal et al, 2008). The reduction of HDL-C in HIV positive of this study confirms report of Bernal et al, (2008), Anastos et al, (2010) and would be due partly to Apo A1 synthesis reduction (Tété-Bénissan et al, 2011), because of immunity collapse (Crowe et al, 2010). In this study, increase of triglycerides in HIV positive is in agreement with report of former studies (Presles, 2006;Pontes-Cardoso et al, 2007;Cournil et al, 2011) which showed that hypertriglyceridemia would be explained by cholesterol and triglycerides transport as lipoproteins.…”
Section: Discussionsupporting
confidence: 80%
“…The important decrease of total cholesterol (hypocholesterolemia) observed among HIV positive patients was induced by pro inflammatory cytokines (interleukines, INF and TNF) accelerating esterified cholesterol accumulation in activated macrophages (Sawadogo et al, 2005;Crowe et al, 2010;Tété-Bénissan et al, 2011). About significant increase of total cholesterol in HIV positive treated with ARV drugs; it was already highlighted by several studies and would be due to a more important disturbance of lipids metabolism (Presles, 2006;Bernal et al, 2008;Anastos et al, 2010;Melzi et al, 2010). Indeed, HIV infection and antiretroviral drugs have independent noxious effects on the blood-vessels and in association, their impact are significantly worsened (Pontes-Cardoso et al, 2007;Bernal et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…After screening, 20 articles met the eligibility criteria [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36] and were included in the analysis (figure 1). Of these, seven 17-23 articles reported incidence of T2DM in HIV-infected participants, eight 24-31 reported prevalence of T2DM in HIV-infected participants compared with uninfected controls and five 32-36 reported prevalence of T2DM in HIV-infected participants on treatment compared with untreated controls.…”
Section: Resultsmentioning
confidence: 99%
“…Details of the RWISA study procedures and informed consent process including video and individual discussion have been previously described. 16 Laboratory data CD4 T lymphocytes counts were determined using the Becton Dickinson FASCount system (Becton Dickinson, Singapore) at the National Reference Laboratory, Kigali, Rwanda and full blood count analyses were performed at King Faisal Hospital in Kigali using CELL-DYN 1800 automated blood analyser (Abbott). A modified methaemoglobin method was used for the colorimetric determination of haemoglobin (Hb).…”
Section: Materials and Methods Study Designmentioning
confidence: 99%